Health Effects of Containing Moral Hazard: Evidence from Disability Insurance Reform - Pilar Garcia-Gomez; Anne C. Gielen (Tinbergen Institute, 2014)
We exploit an age discontinuity in a Dutch disability insurance (DI) reform to identify the health impact of stricter eligibility criteria and reduced generosity. Women subject to the more stringent rule experience greater rates of hospitalization and mortality. A 1,000 reduction in annual benefits leads to a rise of 4.2 percentage points in the probability of being hospitalized and a 2.6 percentage point higher probability of death more than 10 years after the reform. There are no effects on the hospitalization of men subject to stricter rules but their mortality rate is reduced by 1.2 percentage points. The negative health effect on females is restricted to women with low pre-disability earnings. We hypothesize that the gender difference in the effect is due to the reform tightening eligibility particularly with respect to mental health conditions, which are more prevalent among female DI claimants. A simple back-of-the-envelope calculation shows that every dollar reduction in DI is almost completely offset by additional health care costs. This implies that policy makers considering a DI reform should carefully balance the welfare gains from reduced moral hazard against losses not only from less coverage of income risks but also from deteriorated health.
Keywords: I14; H53; I38; 330; disability insurance; moral hazard; health; mortality; regression discontinuity